A Case of Tachycardia and Shortness of Breath. Issue 10 (October 2020) - Kupchik, Nicole; Green, Joel
Abstract : Editor's note: This is the second installment in a new series on electrocardiogram (ECG) interpretation. Nurses in all settings should know the basics, as medications and physiological changes can cause cardiac arrhythmias. Each article will start with a brief case scenario and an ECG strip and then take you step by step through analyzing the heart rhythm.